Membrane Proteins Mediating Reception and Transduction in Chemosensory Neurons in Mosquitoes - Sparks, Jackson T.; Botsko, Gina; Swale, Daniel R.; Boland, Linda M.; Patel, Shriraj S.; Dickens, Joseph C. (Frontiers in Physiology, 2018)
Mosquitoes use chemical cues to modulate important behaviors such as feeding, mating and egg laying. The primary chemosensory organs comprising the paired antennae, maxillary palps and labial palps are adorned with porous sensilla that house primary sensory neurons. Dendrites of these neurons provide an interface between the chemical environment and higher order neuronal processing. Diverse proteins located on outer membranes interact with chemicals, ions and soluble proteins outside the cell and within the lumen of sensilla. Here, we review the repertoire of chemosensory receptors and other membrane proteins involved in transduction, and discuss the outlook for their functional characterization. We also provide a brief overview of select ion channels, their role in mammalian taste, and potential involvement in mosquito taste. These chemosensory proteins represent targets for the disruption of harmful biting behavior and disease transmission by mosquito vectors.